Study on the performance and mechanism of degradation of toluene with non-thermal plasmas synergized supported TiO2/γ-Al2O3 catalyst. Issue 4 (August 2021) - Li, Mengyu; Li, Dandan; Zhang, Ziqi; Ji, Chunjie; Zhou, Shuo; Guo, Wenwen; Zhao, Chaocheng; Liu, Fang; Han, Fenglei
Abstract: The degradation of toluene in dielectric barrier discharge (DBD) reactor packed with supported photocatalysts TiO2 /γ-Al2 O3, Ce-TiO2 /γ-Al2 O3, Ag-TiO2 /γ-Al2 O3, La-TiO2 /γ-Al2 O3, and Co-TiO2 /γ-Al2 O3 was investigated.The supported catalysts were prepared by sol-gel and impregnation methods and were characterized in detail using N2 adsorption, XRD, TEM, XPS and UV-Vis analysis technology. Compared to the non-thermal plasma (NTP) alone system, the degradation rate of toluene and CO2 selectivity improved significantly with the combination of plasma and photocatalysts, meanwhile, the CO selectivity and the by-products NO2 and O3 reduced.When the photocatalyst Ag-TiO2/γ-Al2 O3 was packed into the discharge region, this plasma-photocatalytic system could completely remove toluene with above 81% CO2 selectivity and greatly reduced concentration of poisonous byproducts (O3 and NO2 ) at 5 kJ·L −1, while exhibiting superior stability. The energy efficiency of the hybrid system was increased by about 1.4–3 times, compared with the separated NTP. The main energy loss was the formation of by-products and the loss of light and heat. Finally, the intermediate products of the toluene degradation process of different catalyst systems were analyzed by GC-MS, and the mechanism of toluene degradation by the NTP-photocatalytic system was concluded.The process of NTP synergistic photocatalytic degradation of toluene mainly included three aspects: NTP degradation of toluene, photocatalytic oxidation degradation of toluene, and the synergistic effect between the two. The results can provide a theoretical basis for the study on the performance of VOCs degradation by NTP, and have certain guiding significance for the application and mechanism research of VOCs degradation by NTP. Graphical Abstract: A Non-thermal plasma combined with a photocatalytic reactor was built to study the effect of its synergy with different photocatalysts on toluene degradation, CO2, CO selectivity, and by-product NO2 and O3 concentration. A large number of high-energy electrons was produced during non-thermal plasma discharge. And the chemical bonds would be broken when they were hit by high-energy electrons. The reaction of excitation, dissociation, and ionization generated a large number of active free radicals and oxidizing substances. And the photocatalysts had an interaction with high-energy electrons. Intermediate products and gas-phase reactants were adsorbed on the surface of the catalyst, and the generated free radicals and strong oxidizing substances. The results shows that the synergistic effect of plasma and catalyst can not only improve the conversion rate, but also inhibit the generation of by-products. ga1 Highlights: A Non-thermal plasma combined with a photocatalytic reactor was built to study the synergy effect on toluene degradation. The degradation rate of toluene and CO2 selectivity was improved significantly with the combination of plasma and photocatalyst. The mechanism of toluene degradation by the non-thermal plasma-photocatalytic system was concluded.